Trawling for minnows on the high seas: Criminal law's coercive capacities and the U.S. Maritime Drug Law Enforcement Act - Lynch, Mona Pauline (Punishment & society, 2026)
The Maritime Drug Law Enforcement Act (MDLEA) was passed in 1986 by the U.S. Congress at the height of the American drug war frenzy, further empowering the U.S. government to arrest and prosecute suspected drug traffickers nearly anywhere in the world when transporting drugs by sea. In this article, we use a case study of MDLEA prosecutions in the District of Puerto Rico to identify and delineate five distinct characteristics of criminal law's coercive capacity: (1) jurisdictional capacity; (2) defendant pool capacity; (3) charging capacity; (4) evidentiary capacity; and (5) punishment capacity. While some aspects of the MDLEA are unique, many of these capacious features are inherent to contemporary U.S. criminal law more broadly. Using data from interviews with legal actors, we show how criminal law's capacities work together to ensure convictions and long prison sentences even in the face of formal legal roadblocks. We conclude by suggesting that without scaling back the capacity of such laws, the punitive war on crime in the United States will not only persist but can easily be ramped up to serve political and/or organizational interests.